A new circular economy framework for construction projects. Issue 6 (22nd April 2021) - Medina, Eurica Mae; Fu, Feng
Abstract : Circular economy (CE) is a holistic, viable solution to the 'take-make-dispose of' system of the linear model that enhances economic growth without threatening environmental and social value. Its principles are based on product optimisation, waste elimination and regeneration of natural systems. In this paper, a pilot study evaluates the feasibility of implementing CE in construction projects, followed by the development of a new framework with strategies for altering current construction activities for greater circularity. To demonstrate the benefits of implementing a CE model, a critical assessment of its impacts in the industry was made that considers costing, environmental impacts and legislative action. A new comprehensive CE framework was developed that details a set of indicators, action plans and resources allocated to assess the performance of the strategy implementation, specifically designed for building cycles. To address the challenge of monitoring progress on the transition towards circularity, quantitative tools using a life-cycle approach were developed in this study including an embodied carbon dioxide emission calculator and databases for waste and circularity indexing of common construction materials. The framework, accompanied by these tools, was applied to a construction case study to verify its feasibility in combining scientific and policymaking guidelines. Good practice recommendations were also offered, based on the qualitative research undertaken, to enrich the study further.